(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
With the breakthroughs in information and communication technologies comes a paradigm shift in journalism practice where specialised reporting has taken centre stage in the media industry today. Hence science and technology reporting is a vital area that needs to be given adequate attention by the media and the society. Despite the importance of science and technology reporting to the development of society, its practice is bedevilled with a lot of problems. Using the expository library method of research the paper notes that the science and technology reporter in Nigeria is faced with the problem of capacity building, public illiteracy and phobia of science, lack of a clearly articulated government policy on science and technology and lack of technical, scientific and technological equipment to drive science and technology reporting in the country. The study concludes that because of the importance of this specialised area in journalism government should invest huge material and human resources in terms of funds, provision of specialised training and workshops for journalists to be empowered with the skills required in reporting and disseminating science and technology information to the public.